Diseño y construcción de un prototipo de hidroturbina de rio para evaluación de su desempeño. (2022)
In this study, the design and construction of a river hydroturbine prototype with the Purpose of Assessing Energy Performance Of the same. The necessary objectives are structured to carry out the development of the prototype, Starting from a literature review of existing devices and fluid characterization their dynamics. Furthermore, this device is poses as a laboratory bench use in order to to contribute to the knowledge of the community educational, and product of technological development and innovation.